Analisis Hukum Islam Terhadap Ritual Masyarakat Pra Perkawinan Desa Kalirejo Kecamatan Singorojo Kabupaten Kendal - Wibowo, Eko Setiyo Ary (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
A unique phenomenon, although the Indonesian people, especially in Java, have embraced Islam, it does not eliminate the existence of local culture or traditions in society. Especially in terms of marriage. Because marriage is a very sacred moment, once in a lifetime and an effort to continue offspring, to achieve this goal there are various kinds of rituals that must be carried out by the community. So that it becomes a tradition, namely customs or habits that have been carried out for generations by the community. As is the case, the mupload-mupload tradition in Kalirejo Village, Singorojo District, Kendal Regency. The focus of this research is to find out the process of implementing the mupload-mupload tradition and to review Islamic law on the implementation of the tradition. This research uses empirical or field research, because researchers go directly to the object to be studied, using a qualitative approach, namely making direct observations of phenomena that exist in society. In obtaining the data, the researcher used interview, observation, and documentation methods. That is in the form of primary and secondary data. Data analysis is descriptive in nature which aims to describe the phenomena that exist in the field. The conclusion of this study describes that the factors behind the people of Kalirejo Village, Singorojo District, Kendal Regency carry out the mupload-mupload tradition before marriage, namely traditions or habits, safety, religious spiritual practices, psychology and togetherness. The relationship between Islam and local culture that occurs in the implementation of this tradition takes place in harmony. Which both need and complement each other or undergo a process of assimilation. In the view of ushul fiqh in this case 'urf, the implementation of the mupload-mupload tradition before marriage can still be maintained or preserved, because this tradition can be accepted by human reason and does not contain elements of shirk, so it does not conflict with the Qur'an and Al-Qur'an. Hadith.